PENGARUH PRODUCT PLACEMENT EXPOSURE SAMSUNG GALAXY SERIES PADA VIDEO KLIP BLACKPINK "KILL THIS LOVE" TERHADAP BRAND AWARENESS DAN BRAND PREFERENCE : Survei Pada Followers Aktif Akun Instagram @blinkofficialindonesia - Naomi Yasmine (2020)
Product placement is an advertising strategy that has been around for a long time, but is increasingly being used in recent years. The goal is of course to instill brand awareness and actively promote products advertised by advertisers. This method can be done through a variety of channels, both conventional media and online media. Thanks to the development of the internet, product placement is also inserted in contents that are posted online such as music video. This study aims to determine the magnitude of the effect of product placement exposure of Samsung Galaxy Series in the 'Kill This Love' music video towards brand preferences among BLACKPINK fans through brand awareness as a mediating variable. This study used explanatory quantitative approach. The population in this study was the active followers of @blinkofficialindonesia on Instagram, which is a fanbase of BLACKPINK fans from Indonesia. Researcher used purposive sampling technique to take samples. After calculating the sample using the Yamane formula, 99 samples were obtained. The effect caused by product placement exposure (X) on brand awareness (Z) on the coefficient of determination test is 0,4%, while the remaining 99,6% is caused by other factors. The effect caused by product placement exposure (X) and brand awareness (Z) on brand preference (Y) is 24,2%, while the remaining 75.8% is caused by other factors. From the results of the sobel test calculations, the value of z = 0,651 < 1,980 with a significant level of 5%. Thus, Variable Z is not able to mediate the effect of Variable X on Variable Y with a coefficient of only 0,0216.